Customer value - encounter satisfaction - overall satisfaction: examining the relationship in tourism destinations. (10th February 2020) - Zouni, Georgia; Tsogas, Markos Marios H.; Lykoudi, Dimitra Margieta
Over the past decade, several studies in services and tourism literature have been conducted and concluded that satisfaction is associated and affected by value because value appraisals precede satisfaction. This study aims to examine the relationship between customer satisfaction from each destination service/encounter and overall, and its antecedent, customer value. The proposed relationships are tested using the structural equation modelling (SEM) analysis at an established Greek heritage destination, Olympia. The results indicate that value dimensions can explain considerably the destination service encounter satisfaction, which in turn contributes to overall satisfaction. This study can be considered among the first attempts to empirically test the relationship of service encounter satisfaction from every destination service and customer value.